2022
DOI: 10.3389/fphar.2022.969107
|View full text |Cite
|
Sign up to set email alerts
|

Chuan Huang Fang combining reduced glutathione in treating acute kidney injury (grades 1–2) on chronic kidney disease (stages 2–4): A multicenter randomized controlled clinical trial

Abstract: Lack of effective drugs for acute kidney injury (AKI) grades 1–2 is a crucial challenge in clinic. Our previously single-center clinical studies indicated Chuan Huang Fang (CHF) might have nephroprotection in AKI on chronic kidney disease (CKD) (A on C) patients by preventing oxidant damage and inhibiting inflammation. Reduced glutathione (RG) has recently been shown to increase the clinical effectiveness of high-flux hemodialysis among patients with severe AKI. In this multicenter randomized controlled clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…CKD poses a significant global public health challenge, affecting the quality of life of affected individuals and exerting an economic burden on society. [26,27] Diverse etiologies contribute to the development of CKD, including immune the Clinical Journal of the American Society of Nephrology (1003) and the Journal of the American Society of Nephrology (881). Since most journals were based on the United States dollar, the USA had a powerful influence in the field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CKD poses a significant global public health challenge, affecting the quality of life of affected individuals and exerting an economic burden on society. [26,27] Diverse etiologies contribute to the development of CKD, including immune the Clinical Journal of the American Society of Nephrology (1003) and the Journal of the American Society of Nephrology (881). Since most journals were based on the United States dollar, the USA had a powerful influence in the field.…”
Section: Discussionmentioning
confidence: 99%
“…CKD poses a significant global public health challenge, affecting the quality of life of affected individuals and exerting an economic burden on society. [26,27] Diverse etiologies contribute to the development of CKD, including immune inflammation, metabolic dysregulation, obstruction, and other systemic diseases, ultimately leading to renal fibrosis. [14,28] Renal fibrosis causes irreversible kidney damage, accelerating CKD progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCM formula can also improve AKI. A multicenter randomized controlled clinical trial showed that Chuan Huang Fang formula combined with reduced glutathione can be used to treat AKI (1-2 grades) in CKD patients (2-4 stages) [188]. In addition, Zou et al [189] showed that intestinal flora mediates the protective effect of Qiong-Yu-Gao, a TCM formula, on cisplatin induced AKI by increasing the production of SCFA, thereby inhibiting the expression and activity of histone deacetylase, and reducing the accumulation of uremic toxins.…”
Section: Traditional Chinese Medicine (Tcm)mentioning
confidence: 99%
“…Historically, in the absence of renal replacement therapy (RRT), traditional Chinese medicine (TCM) has been employed to treat kidney disorders in ancient times. Chuan Huang Fang (CHF) is an empirical prescription for the treatment of A on C formulated by Professor Gong Xuezhong at the Shanghai Municipal Hospital of Traditional Chinese Medicine [ 4 , 5 ]. Our previous single-center clinical studies [ 6–8 ] have suggested that CHF may confer renal protective benefits in patients with A on C by reducing oxidative damage and inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%